(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Probiotics have emerged as promising agents in gastrointestinal (GI) cancer therapy due to their ability to modulate signaling pathways, induce apoptosis, produce bioactive compounds, and enhance immune responses. This review synthesizes current evidence on the molecular mechanisms by which probiotics exert anticancer effects, focusing on their regulation of PI3K/AKT, Wnt, and MAPK pathways, induction of cell cycle arrest and apoptosis, production of short-chain fatty acids (SCFAs) and bacteriocins, and mitigation of oxidative stress. These findings underscore the therapeutic potential of probiotics as adjuncts in GI cancer management.